A qualitative exploration of blackness among black South African university students - Albert, Wanelisa Geraldin (Department of Social Development, 2019)
Since the fall of Apartheid, the new mandate of the democratic South African government has been to provide equal quality education for all and to desegregate the education system in South Africa. The desegregation of tertiary education afforded Black students the opportunity to navigate different campuses with vast institutional origins and cultures. This qualitative study aimed to explore Black students' experiences of Blackness while navigating two university campuses in the Western Cape. Drawing upon Black Consciousness and Double Consciousness as the theoretical frameworks, this study examined the experiences and perceptions of Blackness of 20 Black male and female students from two Universities in the Western Cape Province. The aim was to gauge the participants’ sense and understanding of Blackness and how it is shaped and reshaped as they navigate the university space. First, the findings revealed that that Black students exhibited racial pride and ascribed positive traits to Blackness. The students were proud to be Black and asserted that Black people had a good work ethic. Students reported that being Black afforded them an opportunity to change their socio-economic circumstances and improve their communities. Second, Black students who navigated historically White neighbourhoods, schools and university experienced South Africa as untransformed and unequal. On the other hand, Black students who navigated historically Black neighbourhoods, who went to historically Black schools and who attended a majority Black University viewed South Africa as a Rainbow Nation. Black students who attended a historically White university had a heightened sense of Blackness and experienced marginalisation within the university context compared to the Black students who went to a majority Black university Third, universities are not neutral spaces and their historical origins characterise their institutional cultures and the academy. Black students who attended the university founded during colonialism reported that the campus had colonial symbolism and the culture of the university favoured White students. The students reported that the curriculum was Eurocentric and needed to be decolonized. Fourth, Blackness is shaped and reshaped differently on university campuses. Students who went to a majority Black university expressed they were in the majority and the university was a comfortable environment. Black students at both universities experienced racial discrimination and alienation from White and/or Coloured academic staff. Despite progressive policies, this study revealed that much more work need still needs to be done to right the wrongs of the past.